Relevance of holistic anthropology in the understanding of the transition toward urbanisation: a biocultural adaptation - (:unkn) unknown (My University, 2022)
As a biocultural anthropologist who built his interdisciplinary university career in France, I benefited from a postdoctoral experience of international significance (SCHAAR, United Kingdom; DPHRU, South Africa) and also in France (UMR 7206, IRL 3189, UMR 7178) as a continuation of my doctoral project focusing on the role of the urbanization in Senegal in the obesogenic biological transformations of the body and its “obesophobic” socio-cultural conceptions. Such an original approach at the crossroads of different disciplines to account for intrinsically biocultural daily dimensions such as diets, sexual practices or the development of diseases, allowed me to become a permanent research fellow at the CNRS in 2019, through the interdisciplinary committee 52. The heart of my thinking focuses on a holistic – biocultural – understanding of the human body in interaction with the socio-ecological environments that surround it and act on it. Such an attempt to apprehend the human through its entire reality – its body – allows us to envisage the promotion of its well-being. Thus, since the beginning of my career, I have mainly worked through an interdisciplinary perspective on the biocultural determinants and the psychosocial experience of body weight – through the study of diet, body perceptions and physical activity practices – in an environmental context of urbanization among migrants and their descendants in Africa and Europe.I have produced around fifty major publications, written in a wide variety of publication formats, from articles in international impact-factor journals to individual books in French. I have also conducted several research projects in collaboration with trusted complementary partners based in Europe, Africa and North America. In addition, I have supervised many students (including 3 currently in PhD) and taught many courses in biocultural anthropology within a wide variety of university courses. Obtaining the HDR become
Keywords: African Research